Brewery and liquid manure wastewaters as potential feedstocks for microbial fuel cells a performance study - Angosto, J M (Environmental technology, 2015)
This work aims at the comparison of the electrical and chemical performance of microbial fuel cells (MFCs) fed with several types of brewery and manure industrial wastewaters. Experiments were conducted in a single-cell MFC with the cathode exposed to air operated in batch and fed-batch modes. In fed-batch mode, after 4 days of operation, a standard MFC was refilled with crude wastewater to regenerate the biofilm and recreate initial feeding conditions. Brewery wastewater (CV1) mixed with pig-farm liquid manure (PU sample) gave the highest voltage (199.8 mV) and power density (340 mW/m3) outputs than non-mixed brewery waste water. Also, coulombic efficiency is much larger in the mixture (11%) than in the others (2-3%). However, in terms of chemical oxygen demand removal, the performance showed to be poorer (53%) for the mixed sample than in the pure brewery sample (93%). Fed-batch operation showed to be a good alternate for quasi-continuous operation, with equivalent electrical and chemical yields as compared with normal batchwise operation